The Effect of Gender Differences, Locus of Control, and Seniority Auditor on Audit Judgment: Empirical Studies in East Jakarta Public Accounting Firms - Manurung, Laura Asido Rohani; Hasbi, Muhammad (Santoso Academy Network, 2023)
This study aims to examine the effect of Gender, Locus of Control, and Senior Auditor on Audit Judgment. The sample in this study were auditors who worked at the East Jakarta Regional Public Accounting Firm. This research is quantitative. This study used a questionnaire given or distributed directly by researchers to auditors who work in several East Jakarta KAPs by visiting the office. Data were analyzed using multiple regression. The results of this study indicate that 1) Gender has no effect on audit judgment, 2) Locus of Control has a positive influence on audit judgment, 3) Seniority Auditor has a positive influence on audit judgment, and 4) Gender, Locus of Control, and Seniority Auditor simultaneously affects the audit assessment. This research implies that it can be used as development materials and knowledge in accounting, especially in auditing, especially in the field of audit interest judgment. For the development of science, it is better to review an auditor's performance in making an audit judgment to identify new factors as possible influences on audit judgment.